Cyprus : ethnic conflict and international politics - Joseph, Joseph L. (Hampshire : Macmillan, 1997)
Includes bibliographical references and index
Keywords: Cyprus -- Ethnic relations; Cyprus -- Foreign relations; Cyprus -- Politics and government -- 1960-.